2021
DOI: 10.1200/jco.2021.39.15_suppl.5072
|View full text |Cite
|
Sign up to set email alerts
|

Real-world first-line (1L) treatment patterns in patients (pts) with metastatic castration-sensitive prostate cancer (mCSPC) in a U.S. health insurance database.

Abstract: 5072 Background: Over the past 6 years, intensification of androgen deprivation therapy (ADT) with docetaxel (DOC) and novel hormonal therapies (NHT) [abiraterone, enzalutamide, and apalutamide], has been shown to improve survival outcomes in men with mCSPC. This study assessed the real-world utilization of effective combination therapies as 1L treatment in insured pts in the U.S. with mCSPC. Methods: This retrospective study used the Optum health insurance claims database, which includes pt claims data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
0
15
0
2
Order By: Relevance
“…Likewise, Swami and colleagues [32] found that US patients in the Optum health insurance claims database who received chemotherapy (docetaxel) + ADT or NHA + ADT were younger (mean 68 and 73 years, respectively) than patients who received ADT alone (mean 75 years), although, unlike in the present survey, a greater proportion of patients with more aggressive disease (i.e., visceral metastases) received ADT alone (55%) vs chemotherapy + ADT (9%) or NHA + ADT (17%). Younger age in chemotherapy + ADT-treated men with mHSPC was also observed by Tagawa et al [33], who also found that patients treated with NHA (abiraterone) + ADT or chemotherapy (docetaxel) + ADT were more likely to have metastatic disease in lymph nodes (also observed in our survey) and other sites at treatment initiation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Likewise, Swami and colleagues [32] found that US patients in the Optum health insurance claims database who received chemotherapy (docetaxel) + ADT or NHA + ADT were younger (mean 68 and 73 years, respectively) than patients who received ADT alone (mean 75 years), although, unlike in the present survey, a greater proportion of patients with more aggressive disease (i.e., visceral metastases) received ADT alone (55%) vs chemotherapy + ADT (9%) or NHA + ADT (17%). Younger age in chemotherapy + ADT-treated men with mHSPC was also observed by Tagawa et al [33], who also found that patients treated with NHA (abiraterone) + ADT or chemotherapy (docetaxel) + ADT were more likely to have metastatic disease in lymph nodes (also observed in our survey) and other sites at treatment initiation.…”
Section: Discussionmentioning
confidence: 97%
“…Previous real-world investigations in the US, evaluating care in mHSPC patients who initiated treatment between 2014 and 2019, reported that overall (i.e., over the entire period), ADT alone was the most common mHSPC regimen initiated, with rates ranging from 47 to 63%. In contrast, NHA use over the same period was low (5-14%) [30][31][32][33], although this finding is unsurprising given that NHAs in the mHSPC setting did not receive US Food and Drug Administration approval until 2018-2019. Indeed, Ke et al [31] reported that mHSPC patients in their 2017-2018 cohort were less often receiving ADT alone (43% vs 52%) and more often abiraterone (10% vs 4%) as initial regimen compared with the 2015-2016 cohort.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Upfront intensification not only prolongs life but does so without compromising quality-of-life as observed in randomized clinical trials [13]. However, retrospective studies (mostly as abstracts) from multiple different databases including Optum, Medicare and ConcertAI Oncology Dataset have shown a consistent underutilization of intensification ranging from < 10% to up to 30% of mCSPC patients and even those with visceral disease and in those with insurance [14][15][16][17]. In our dataset, we confirm that upfront intensification was low but a gradual and encouraging trend towards increased intensification was observed over the last 5 years (Figure 3).…”
Section: Discussionmentioning
confidence: 99%